The Impact of Scholarships on Students' Career Development: A Comparative Study in Higher Education Institutions - Salsabila Farahdiva; Steven Apriliardo; Regina Tira Julianti; Karyanti Karyanti; Asep Solikin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Background: Higher education plays a crucial role in improving the quality of human resources. However, not all students have equal access to resources, particularly in terms of educational financing. Scholarships serve as one solution to expand access, yet their impact on students' career development has not been widely examined. Aim: This study analyzes the relationship between scholarship status and students' career development. Method: The method employed is a quantitative, comparative design that compares scholarship recipients and non-recipients across career development categories. Results and Discussions: The results indicate that scholarship recipients tend to demonstrate better career development, with the majority falling into the